Horizontes experimentais da arquitetura: práticas espaciais contra hegemônicas em arquivos latino-americanos 1960-1990 - Gabriela Pires Machado (2020)
This thesis provides an overview on the critical cartography of Latin American spatial practices during the period beginning in 1960 to 1990, under the possible horizon concept (CAMPOS, 1969) that expands itself in order to incorporate the past into the present. It also challenges the hegemonic paradigm and the architecture and urbanism tautological tradition. It proposes to rethink the spatial experimental concept, and tackles the discipline intersecting, applying stress to the knowledge field towards articulated emancipatory gestures from decentrednesses narrations. Creating a digital archive for common use, it coordinates documents and images that claims territory as imagination and memory political settings transmitted by agents and devices into a field of spatial practices organized into potential zones. The proposed digital archive was thought as an open course to reading and problematizing narrations and documents under the decolonial perspective and it provides critical devices that enlarge the discourse field of architecture and urbanism in order to think Latin America beyond the global north hegemonic referential. Those spatial practices came from the close relationship between aesthetics and politics in the social political context of the period. They incorporate symbolical local shapes and potentialize strategies and languages that allow to understand territory under disputes that still happen. Coordinated into two parts – Memory Writings and Latin American Contextures – it aims to evinces the contraditions from archive, history and memory in spatial violent contexts and their visible and invisible narration shapes in representative systems. We invite you to revisit thinkers, concepts and works made in Latin American territory in order to rewrite history – a kind of speculative and collaborative adventure - that can reconfigurate and redistribute knowledge under other epistemological conditions.